Screening of polymorphic random amplified polymorphism DNAs (RAPDs) markers for the amplification of physalis minima DNA - Joshua, Stefan Nyua (2010)
Cape gooseberry or Physalis minima is from the Solanaceae family and originates from Central South America. In European countries the fruit which resembles cherry tomatoes are widely used as vegetables. It is considered as weeds in Malaysia despite the medicinal value and high vitamin C content. This plant has the potential as cultivated crop. Prior to cultivation, the fundamental aspects are required and one of it is the genetic profile. Molecular tools are widely used in genetic studies and Random Amplified Polymorphism DNA (RAPDs) is one of the early PCR based marker. It is favourable because it is a dominant marker, easy to use and randomly amplified genomic DNA. A study was carried out to determine the genetic variation of P. minima from two populations with the objectives of (1) to screened 10 OPA and 20 OPB RAPD primers for amplification of P. minima DNA and (2) to obtain polymorphic RAPD primers for P. minima.. DNA extraction was carried out using GeneAll® Plant DNA extraction kit and quantification was done using spectrophotometer. Polymerase chain reaction (PCR) was carried out in a total volume of 25 μL consisting of 30 ng of genomic DNA, 10× PCR Mastermix, 10× PCR Buffer, 0.2 μM of the primers and distilled water. Amplifications were carried out in a thermalcycler programmed, with an initial step at 94°C for 3 minutes, followed by 40 cycles of 60 seconds at 94°C; 60 seconds at 43.6°C, and 120 seconds at 72°C, followed by a cycle of final extension step of 10 minutes at 72°C. From this study a total of 11 OPA primers and 20 OPB primers were obtained that showed positive amplification on P. minima DNA band.